FEEDBACK OF WATER STRESS ON WOOD PROPERTIES OF TREES: EXPERIMENTS WITH MISTLETOES ON RHODODENDRON ARBOREUM SM. - Devkota, Mohan P.; Glatzel, Gerhard (Ecoprint: An International Journal of Ecology, 2004)
Effects of infection by the mistletoe Scurrula elata (Edgew.) Danser, on wood properties of its common host Rhododendron arboreum Sm., were studied in the Annapurna Conservation Area of Central Nepal Himalaya. Heavy infection by mistletoes invariably causes decline of the host. Infested branches show inhibition of growth, defoliation and eventual death of branch parts distal to the site of infection. Anatomical properties of wood were compared in samples of branches proximal to the infection and in uninfected branches. The hypothesis that infection induces changes in basic wood anatomy could not be proven. Vessel density, vessel area, percentage lumen area and mean vessel diameter of the wood of infested and uninfected branches did not show any significant differences. The studied anatomical parameters were not correlated to the diameter of the host branch. These results show that infection by S. elata did not cause any changes in basic wood anatomy of its host R. arboreum. It appears that the studied anatomical parameters of Rhododendron wood are fairly stable and are not changed by stress due to infection by mistletoes. The damage to the host distal to the infected area most likely results from an insufficiency of total conductive area to supply both mistletoe and host. Unfortunately we could not determine annual conductive area increment, because R arboreum does not develop usable annual tree rings in the climate of the study area.Key words: Himalayas, mistletoe. Rhododendron arboreum, Scurrula elata, water stress, wood anatomy. Ecoprint Vol.11(1) 2004.